Implementation of DIKW-Based Business Intelligence Using Google Looker Studio for Data-Driven Decision-Making in Babakanmulya Village - Aditya Nugraha Yesa; Muhammad jazman; Muhammad Afdal; Inggih Permana (SemanTIK : Teknik Informasi, 2025)
Sustainable village development requires a data-driven approach to enhance transparency and the effectiveness of public services. However, one of the challenges faced by the Babakanmulya village government is the inability to make well-informed decisions due to the available data being in raw form and not yet processed into meaningful information. This study aims to design and implement a Business Intelligence dashboard using Google Looker Studio by integrating the DIKW (Data, Information, Knowledge, Wisdom) framework in managing village community data. By collecting demographic, economic, educational, and health data, this research transforms raw data into relevant and easily understandable information. The analysis of this information provides deep insights into the community's social and economic conditions as well as their participation in government programs. Consequently, village authorities can make more informed and data-driven decisions to formulate more effective policies that enhance community welfare. The implementation of automated reporting using Google Apps Script also ensures that up-to-date information can be delivered to stakeholders in a timely manner. This study demonstrates that applying the DIKW framework in a Business Intelligence dashboard can improve the planning and execution of village development in a more responsive and inclusive manner while assisting the village government in overcoming data-driven decision-making challenges.